Russian-Speaking Population in Far-Abroad Countries - S. V. Ryazantsev; E. E. Pismennaya; G. N. Ochirova (Vestnik MGIMO-Universiteta)
Attracting compatriots living abroad is strategically vital in the context of continuing depopulation in Russia. However, a multilayered definition of the category of a compatriot creates blurred boundaries. As a result, it is somewhat problematic to assess the number of Russian compatriots living abroad objectively. The paper presents the results of a study of the socio-demographic structure of the Russian-speaking population in far-abroad countries. The statistical data of Rosstat, the UN, Eurostat, OECD, and national statistical services of foreign countries were analyzed to assess the number of Russian-speaking populations and determine the main emigration channels and geography of resettlement. Within the study, the authors have conducted an expert survey of the Ministry of Foreign Affairs of the Russian Federation, the Embassies of the Russian Federation, and representative offices of Rossotrudnichestvo in foreign countries. The survey results indicate the heterogeneous structure of Russian-speaking communities by reasons of emigration, socio-economic status, degree of integration into the host society, gender, and ethnic composition, and geography of resettlement. However, state policy analysis towards compatriots shows that it targets people who already demonstrate an interest in Russia, participate in Russian-speaking organizations, and get involved in cultural, religious, and sports events. There is a need for cooperation and interaction with Russian-speaking people. Moreover, given that young people adapt and get integrated more efficiently, it is essential to prevent the loss of cultural capital of Russian-speaking youth living abroad. It is necessary to develop and implement a more differentiated approach towards interaction with the Russian-speaking population.